High-Level and Efficient Stream Parallelism on Multi-core Systems with SPar for Data Compression Applications - Griebler, Dalvan; B. Hoffmann, Renato; Loff, Junior; Danelutto, Marco; Gustavo Fernandes, Luiz (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2017)
The stream processing domain is present in several real-world applications that are running on multi-core systems. In this paper, we focus on data compression applications that are an important sub-set of this domain. Our main goal is to assess the programmability and efficiency of domain-specific language called SPar. It was specially designed for expressing stream parallelism and it promises higher-level parallelism abstractions without significant performance losses. Therefore, we parallelized Lzip and Bzip2 compressors with SPar and compared with state-of-the-art frameworks. The results revealed that SPar is able to efficiently exploit stream parallelism as well as provide suitable abstractions with less code intrusion and code refactoring.